1994
DOI: 10.1016/0361-9230(94)90208-9
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase activity in the preoptic area differs between aggressive and nonaggressive male house mice

Abstract: Treatment with testosterone (T) or estradiol (E2) facilitates intraspecific aggressive behavior in adult rodents. Brain aromatization of T to E2 appears to be involved in facilitation of fighting behavior. In the present study we measure the in vitro brain aromatase activity (AA) in the preoptic area (POA), amygdaloid nuclei (Am), ventromedial hypothalamus (VMH), and parietal cortex (CTX) from two strains of adult male house mice, which were genetically selected for territorial aggression, based upon their att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…T can act either directly via binding to androgen receptors (ARs), or indirectly via binding to estrogen receptors (ERs) after aromatization into 17 -estradiol (E2) within the brain. Indeed, numerous studies have shown the importance of T, its estrogenic metabolite E2, and the enzyme aromatase (AROM) for the regulation of sexual and aggressive behaviors during the reproductive season (Hutchison, 1971;Schlinger and Callard, 1990;Monaghan and Glickman, 1992;Compaan et al, 1994;Balthazart et al, 1997;Ball and Balthazart, 2004;Scordalakes and Rissman, 2004). Birds have proven to be excellent systems to study seasonal changes in physiology and behavior both in the field and in the laboratory (Ball and Balthazart, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…T can act either directly via binding to androgen receptors (ARs), or indirectly via binding to estrogen receptors (ERs) after aromatization into 17 -estradiol (E2) within the brain. Indeed, numerous studies have shown the importance of T, its estrogenic metabolite E2, and the enzyme aromatase (AROM) for the regulation of sexual and aggressive behaviors during the reproductive season (Hutchison, 1971;Schlinger and Callard, 1990;Monaghan and Glickman, 1992;Compaan et al, 1994;Balthazart et al, 1997;Ball and Balthazart, 2004;Scordalakes and Rissman, 2004). Birds have proven to be excellent systems to study seasonal changes in physiology and behavior both in the field and in the laboratory (Ball and Balthazart, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3), and this functional connection might also help explain the aggressive tendencies of individuals from this temperature. The POA plays an important role in the expression of aggression in rodents [Albert et al, 1986;Compaan et al, 1994], and lesions of the AH-POA continuum abolish agonistic behaviors in male green anole lizards [Wheeler and Crews, 1978]. In all lizards studied to date, both areas also either express the genes for sex steroid receptors [Young et al, 1994] or concentrate sex steroids [Morrell et al, 1979].…”
Section: Functional Connectivity and Intrasexual Differences In Aggrementioning
confidence: 99%
“…For example, intermale aggression in most rodents is facilitated by testosterone, or its aromatization to estradiol (Compaan et al, 1994), whereas the expression of maternal aggression is facilitated by estradiol, progesterone, and prolactin released during pregnancy and lactation (Bridges, 1996;Mann et al, 1984;Stern and McDonald, 1989), as well as sensory input (including olfactory and tactile stimuli) to the lactating females from pups (Lonstein and Gammie, 2002;Stern and Kolunie, 1993;Svare et al, 1980). Additionally, certain neuromodulators have different effects on maternal and male aggression.…”
mentioning
confidence: 99%